Comparison of eosin-thiazin and Papanicolaou-Shorr staining for endometrial cytologies of broodmares - Walter, J.; Klein, C.; Wehrend, A. (Tierärztliche Praxis Ausgabe G: Großtiere / Nutztiere, 2011)
Introduction: Exfoliative endometrial cytology is an easy and valuable diagnostic tool for the detection of inflammatory processes of the uterus that correlates well to culture results. The practical use of this procedure is limited due to the time-consuming Papanicolaou-Shorr staining technique. In this study the suitability of the rapid eosin-thiazin staining for endometrial smears was investigated. Material and methods: Sample collection was carried out with a guarded culture swab (Knudsen-catheter) in 27 broodmares during routine gynaecological examination. Two smears were prepared from each collection. One was stained according to Papanicolaou-Shorr and the second using the eosin-thiazin method (Hemacolor®, Merck). Specimens with more than 0.5% neutrophil granulocytes were classified as positive for endometritis. The presentability of polymorphonuclear neutrophils (PMN), proportion of positive/negative samples, as well as the PMN contents were compared between the two staining methods. Results: PMN were easily identifiable in both specimens. In Papanicolaou-Shorr stained smears 10 samples showed > 0.5% neutrophil granulocytes (37%), whereas in the eosin-thiazin staining 12 samples were positive (44%). Thus results corresponded in 25 mares (95%). Conclusion: Eosin-thiazin staining is a suitable staining method for endometrial smears of broodmares, which surpassed Papanicolaou-Shorr method in two cases. Clinical relevance: The use of eosin-thiazin staining provides a considerable gain of time and renders endometrial cytology more attractive for routine stud farm practice.
Keywords: Endometritis; neutrophil granulocytes; PMN; endometrial swab; staining methods